Mandates and Penalties: The Impact of Policy Implementation on Biofuel Markets - A Comparative Study on Road and Aviation Transport Fuel Prices in Different EU Countries - Forslund, Sunna (My University, 2025)
To achieve the European Union’s goal of climate neutrality by 2050, substantial reductions in greenhouse gas (GHG) emissions are required in the domestic transport sector. One way to support this transition is to decrease the use of fossil fuels by increasing the share of biofuels through blending mandates. All EU-27 Member States have implemented national biofuel blending mandates for road transport fuels, while by 2022, only France and Sweden had introduced such mandates for aviation fuel. This thesis aimed to map penalties for non-compliance with biofuel blending mandates in the road transport and aviation sectors across EU Member States, and to assess their impact on fuel prices. Based on penalty levels, the study estimated the corresponding effects on biofuel prices to investigate how much fuel suppliers are willing to pay to avoid penalties. Furthermore, a comparison between theoretical fuel prices and actual consumer prices has been conducted. Lastly, this thesis examined whether there is a correlation between penalty levels and the degree of compliance with biofuel blending mandates. The findings highlighted how penalty levels vary in both size and formation across EU Member States. Most countries apply per-unit penalties in the road transport sector, while others impose fines of judicial measures, and for a few could no penalties at all be found. Biofuel mandate threshold prices (i.e., what fuel suppliers would be willing to pay for biofuels to avoid the penalty) were calculated and connections to the penalty level were identified. This was also reflected in the consumer prices of blended fuel, as higher biofuel mandate threshold prices resulted in higher theoretical consumer prices. These were generally higher than actual prices, suggesting that in most countries, fuel suppliers were not forced to pay the full biofuel mandate threshold price. Lastly, this thesis highlighted how biofuel blending mandates and penalties are implemented in different formulations and levels across EU Member States. However, penalty levels do not necessarily correspond directly to the degree of fulfilment of the mandate. In general, the implementation of biofuels is more widespread in the road transport sector than in aviation, which could be the result of more developed markets for road transport biofuels.
Keywords: biofuel policy; GHG emission reduction; transport sector; penalty; blending obligation